Pendampingan Penyusunan Artikel pada Mahasiswa Guna Meningkatkan Kemampuan dalam Menulis dan Publikasi : Assistance in Preparing Articles for Students to Improve Their Writing and Publication Skills - Tamrin Fathoni (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
The purpose of preparing this work is to assist students in writing articles to improve their writing and publication skills. The ABCD method, which includes Needs Analysis, Forms of Mentoring, Process Analysis Methods, and Personal and Group Support, is the main basis for guiding Islamic Religious Education students at INSURI Ponorogo in improving their writing and publication skills through careful and holistic mentoring strategies. The results of this work reflect comprehensive assistance steps in improving the writing and publication skills of students in the Islamic Religious Education Study Program. In the initial stage, high enthusiasm can be seen through understanding the material, discussing ideas, and guiding literature. Article assistance begins with planning, guiding the structure of the article, and developing research skills. When writing drafts, students are guided in understanding the topic, intensive feedback, and strengthening the logic of scientific publications. The revision stage includes checking the narrative flow and critical analysis, aimed at improving the quality of the article. Language and writing style assistance involves language continuity and grammatical considerations. Journal selection is discussed in depth, increasing students' practical understanding. Preparation for publication involves guiding article submissions to journals, providing support in editorial responses, and helping students develop as writers and researchers. This assistance aims to achieve quality articles and increase students' self-confidence in the academic world.